Pengaruh Gaya Kepemimpinan Demokratis dan Motivasi Kerja terhadap Kompetensi Serta Dampaknya pada Kinerja Pegawai Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Tanjung Jabung Timur - Astuti, Herlina Dwi; MS, M. Zahari; Yamali, Fakhrul Rozi (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to enable researchers to determine the influence of democratic leadership style and work motivation on employee performance mediated by competency at the Public Works and Spatial Planning Department of East Tanjung Jabung Regency. This research uses the PLS analysis method. Based on the results of the questionnaire, the democratic leadership style is in the good category. Then for work motivation in the very high category. Furthermore, competency is in the Very High category. Meanwhile, employee performance is in the high category. Based on the research results, democratic leadership style has no significant effect on competence, work motivation has a significant and positive effect on competence, democratic leadership style has a significant effect on employee performance, work motivation has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance, Democratic leadership style does not have a significant effect on employee performance through competence and work motivation has a significant and positive effect on employee performance through competence in the Public Works and Spatial Planning Department of East Tanjung Jabung Regency.Â